Social Pressure-Induced Craving in Patients with Alcohol Dependence: Application of Virtual Reality to Coping Skill Training - Lee, Jung Suk; Namkoong, Kee; Ku, Jeonghun; Cho, Sangwoo; Park, Ji Yeon; Choi, You Kyong; Kim, Jae-Jin; Kim, In Young; Kim, Sun I.; Jung, Young-Chul (Psychiatry investigation, 2008)
This study was conducted to assess the interaction between alcohol cues and social pressure in the induction of alcohol craving. Fourteen male patients with alcohol dependence and 14 age-matched social drinkers completed a virtual reality coping skill training program composed of four blocks according to the presence of alcohol cues (x2) and social pressure (x2). Before and after each block, the craving levels were measured using a visual analogue scale. Patients with alcohol dependence reported extremely high levels of craving immediately upon exposure to a virtual environment with alcohol cues, regardless of social pressure. In contrast, the craving levels of social drinkers were influenced by social pressure from virtual avatars. Our findings imply that an alcohol cue-laden environment should interfere with the ability to use coping skills against social pressure in real-life situations.